Blood hemoglobin A1c might predict adverse differences in heart rate variability in a diabetic population: Evidence from the Midlife in the United States (MIDUS) study - Huang, Ying; Chen, Hong; Hu, Dongxia; Wan, Rong (Frontiers in Endocrinology, 2022)
Background Cardiac autonomic neuropathy in population with diabetes mellitus (DM) is frequent and linked with high risk of cardiovascular mortality. However, studies on whether blood hemoglobin A1c (HbA1c) levels are related to adverse differences in heart rate variability (HRV) in individuals with DM are scarce. Aim We aimed to investigate the association of blood HbA1c levels with adverse differences in HRV, which is an indicator of cardiac autonomic control, in adult individuals with and without DM. Methods Data were collected from the Midlife in the United States (MIDUS) study, and 928 individuals were analyzed for the relationship between blood HbA1c levels and HRV through a cross-sectional analysis. Results Participants with DM had significantly higher HRV than those without DM. The smooth curve suggested inverse relationships between blood HbA1c levels and HF- and LF-HRV seen in participants with DM but not in those without DM after controlling for all covariates (age, sex, BMI, smoking, number of drinking years and exercise). Furthermore, linear regression analysis demonstrated that elevated blood HbA1c levels did contribute to adverse differences in HF-HRV (Sβ= -0.118; 95% CI -0.208, -0.027; P=0.012) and LF-HRV (Sβ= -0.097; 95% CI -0.177, -0.017; P=0.019) after controlling for these covariates in participants with DM, while in participants without DM, blood HbA1c was not significantly related to adverse differences in HF-HRV (Sβ=0.095; 95% CI -0.059, 0.248; P=0.228) or LF-HRV (Sβ=0.043; 95% CI -0.103, 0.189; P=0.565). DM has a significant modifying effect on associations between blood HbA1c and adverse differences in HF-HRV (P for interaction=0.019) and LF-HRV (P for interaction=0.029). Conclusions We reported strong evidence that elevated blood levels of HbA1c were associated with adverse differences in HRV in the diabetic population but not in the nondiabetic population. This finding supported that long-term hyperglycemia is related to autonomic nerve injury in the diabetic population. Blood HbA1c might be a good indicator of cardiac autonomic neuropathy.